Synthesis of the diarylindolizidine alkaloid (+)-Fistulopsine B: Application of an organocatalytic Michael addition reaction. Issue 13 (29th March 2018) - Moorthy, N.V.G.; Pansare, Sunil V.
Abstract: The first synthesis of a recently isolated antiproliferative diarylindolizidine alkaloid, (+)-fistulopsine B, was achieved. The synthesis features the use of an organocatalytic ketone-nitrostyrene Michael addition as the key step. Graphical abstract: The first, enantioselective synthesis of the diaryl indolizidine alkaloid (+)-fistulopsine B was achieved from a key γ-nitroketone which is easily prepared by an organocatalytic Michael addition.